Analisis Fungsi Empat Isim Tawābi' dalam Kitab Al-Ajurumiyyah Perspektif Ilmu Nahwu - Adhawa Astiwa; Agni Mafatiha Fatimah; Muhamad Fikri Roshif (Jurnal Budi Pekerti Agama Islam, 2026)
This study aims to analyze the syntactic function of the four isim tawābi' na'at, taukīd, 'aṭaf, and badal in Kitab Al-Ajurumiyyah*, a classical foundational text of Arabic syntax (nahwu) widely taught in Indonesian Islamic boarding schools (pesantren). The background of this research is grounded in the persistent difficulty faced by beginner learners in distinguishing the four types of* tawābi' and applying their i'rab (syntactic case marking) rules correctly. This study employs a qualitative descriptive method with a library research (content analysis) approach, using Kitab Al-Ajurumiyyah as the primary data source and relevant scholarly journal articles published between 2020–2024 as secondary sources. The findings indicate that each type of tawābi' possesses a distinct syntactic function: na'at serves an attributive function, taukīd serves an emphatic function, 'aṭaf serves a conjunctive function, and badal serves a substitutive/appositive function — yet all four share the same fundamental rule of following their matbū' (the noun they modify) in i'rab, definiteness, gender, and number. The pedagogical implication of this study is the need for a systematic and comparative teaching approach to the four* tawābi' so that beginner learners can more easily distinguish their syntactic functions within Arabic sentence structures.